О зависимостях характеристик поверхностной энергии у некоторых материалов, содержащих элементы IV – VI групп - Осипов, А. Д. (НТУ "ХПИ", 2014)
Показано, что величины поверхностной энергии у ряда материалов, содержащих элементы IV-VI групп в значительной мере определяются комплектами функций, включающих характерные атомно-электронные величины.

It is demonstrated that the characteristics of surface energy in some materials, which include elements of the IV-VI groups are signigicantly determined by the complete series of functions of effective potentials including characteristic values of atomic and electronic quantities.
About dependancies characteristics of surface energy in some materials, which include elements IV – VI group
Keywords: зависимости эффективных потенциалов; комплект функций; воздействие; surface energy; effective potentials